Hubungan Supervisi Akademik Kepala Sekolah, Komunikasi Interpersonal, dan Etos Kerja dengan Kinerja Guru di SDN Kecamatan Banjarbaru Utara - Faisal Akbar; Aslamiah Aslamiah; Ahmad Muhyani Rizalie (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This study aims to describe the principal's academic supervision activities, interpersonal communication, work ethic, and teacher performance; and analyze the direct and indirect relationship between the principal's academic supervision, interpersonal communication, and work ethic with the performance of elementary school teachers in North Banjarbaru District, Banjarbaru City. This research is a quantitativ research. The sample size of this study was 172 teachers. Data collection instruments in the form of questionnaires that have met the requirements of validity and reality tests. Data analysis to test the relationship in this study used path analysis. Based on the results of this study, it was found that there is a direct relationship between: academic supervision of the principal with teacher performance, interpersonal communication with teacher performance, work ethic with teacher performance academic supervision of the principal with work ethic, interpersonal communication with work ethic; and the indirect relationship between the principal's academic supervision and teacher performance through work ethic, interpersonal communication with teacher performance through work ethic.academic principal, interpersonal communication, work ethic and performance of elementary school teachers in North Banjarbaru District, Banjarbaru City Keywords: Principal's academic supervision, interpersonal communication, work ethic, teacher performance